CCL3L1 copy number is a strong genetic determinant of HIV seropositivity in Caucasian intravenous drug users. - Huik, Kristi; Sadam, Maarja; Karki, Tõnis; Avi, Radko; Krispin, Tõnu; Paap, Piret; Rüütel, Kristi; Uusküla, Anneli; Talu, Ave; Abel-Ollo, Katri; Lutsar, Irja (The Journal of infectious diseases, 2010)
A high copy number of CCL3L1, the most potent human immunodeficiency virus (HIV)-suppressive chemokine, associates with reduced HIV susceptibility. Whether CCL3L1 influences acquisition of multiple blood-borne infections (eg, hepatitis C virus [HCV], HIV, and hepatitis B virus [HBV] infections), which occur commonly among injection drug users (IDUs), is unknown.
Keywords: Adult; Chemokines, CC; Drug Users; Estonia; European Continental Ancestry Group; Female; Gene Dosage; Hepacivirus; Hepatitis C; HIV Seropositivity; Humans; Immunity, Innate; Male; Polymerase Chain Reaction; Substance Abuse, Intravenous